EDITORIAL EDIÇÃO ESPECIAL - GRITOS NA QUARENTENA - de Vasconcelos Machado Guimarães, Ludmila; Carreteiro, Teresa Cristina; Rochael Nasciutti, Jacyara (Caderno de Administração, 2020)
Editorial do volume 28, Edição Especial, 2020.